2019
DOI: 10.1080/14480220.2019.1685161
|View full text |Cite
|
Sign up to set email alerts
|

Exploring agricultural vocational pedagogy in Uganda: students’ experiences

Abstract: Increasingly studies claim that building young people's vocational interest in agriculture, as a sector of meaningful employment, is a central dilemma of Africa's education and labour market systems. With Ugandan students' voices, this article examines some of the methodological dilemmas of agricultural education and training. The article draws from evidence generated through a qualitative case study of a public agricultural college. We undertook the study in line with our conceptual argument for mainstreaming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Relatedly, the World Bank reported that feedback from Ugandan employers indicated that current training programmes were failing to equip trainees with practical skills and job-relevant competencies (World Bank, 2012). It is equally evident that tertiary AET institutions most times teach agriculture theoretically with negligible students' exposure to practice (Jjuuko et al, 2019).…”
Section: Vocational Placements In Uganda's Tertiary Educationmentioning
confidence: 99%
“…Relatedly, the World Bank reported that feedback from Ugandan employers indicated that current training programmes were failing to equip trainees with practical skills and job-relevant competencies (World Bank, 2012). It is equally evident that tertiary AET institutions most times teach agriculture theoretically with negligible students' exposure to practice (Jjuuko et al, 2019).…”
Section: Vocational Placements In Uganda's Tertiary Educationmentioning
confidence: 99%
“…In its place, short-term and topic-specific training was the main instrument to improve farmers' knowledge and agricultural practices, and young farmers learned farming techniques from their parents (Šūmane et al 2018;Afere et al 2019;ILO and UNESCO 2019). However, evidence shows that short-term training (lasting a few days or weeks) alone does not sufficiently qualify young farmers and other professionals in the agrifood sector, nor in the rural sector as a whole (Haggblade et al 2015;Minde et al 2015;Eissler and Brennan 2015;Brewer and Comyn 2015;O'Donoghue and Heanue 2018;Jjuuko, Tukundane, and Zeelen Source: Kirui and Kozicka (2018).…”
Section: Figure 91-actors In Technical and Vocational Education And Training In Africamentioning
confidence: 99%
“…The agency freedom and professional autonomy of frontline social actors, especially the AET educators, to practice craftsmanship, democracy and associated transformative approaches is an equally key core argument. Finally, I restate the claim that worrying about the negative influence of dispositional factors, including assumed lack of interest in agriculture education and work as key drivers of limited youth labour market transition, is indeed only one side of the coin (Jjuuko, Tukundane, & Zeelen, 2019). On the other side should be the great concern about how AET institutions and the entire agriculture industry are structured to support the agentic participation of young people.…”
Section: Youth Transition Agricultural Education and Employment In Ugandamentioning
confidence: 88%
“…Under chapter five I present a detailed account of the state of agriculture education practice at the AET institutions as derived from experiences and perceptions of frontline social actors of the seven VTIs and the case study AET institution. Also, in the article on 'Exploring agricultural vocational pedagogy in Uganda: Students' experiences' published by the International Journal of Training Research (Jjuuko, Tukundane, & Zeelen, 2019), the experiences are used to strengthen the arguments for a craftsmanship embedded vocational pedagogy in Uganda and similar contexts.…”
Section: State Of Agri-education Practicementioning
confidence: 99%
See 1 more Smart Citation